Sonate pour le pianoforte : oeuv. 111 ... composeé et dédiée à son altesse imperiale Monseigneurl'Archiduc d'Autriche, Cardinal et Prince Archeveque d'Olmütz etc. par Louis van Beethoven - Beethoven, Ludwig van, 1770-1827 (composer)::::::::::::::: (Jean Aug. Böhme; Germany; Hamburg, 2022)
Edition of the Piano Sonata no. 32 in C major, op. 111, published in an unnamed series by Jean Aug. Böhme in Hamburg. With decorative passé-partout title page. Plate number 869.